1997
DOI: 10.1590/s0100-879x1997000300005
|View full text |Cite
|
Sign up to set email alerts
|

Control of the phosphorylation of the astrocyte marker glial fibrillary acidic protein (GFAP) in the immature rat hippocampus by glutamate and calcium ions: possible key factor in astrocytic plasticity

Abstract: The present review describes recent research on the regulation by glutamate and Ca 2+ of the phosphorylation state of the intermediate filament protein of the astrocytic cytoskeleton, glial fibrillary acidic protein (GFAP), in immature hippocampal slices. The results of this research are discussed against a background of modern knowledge of the functional importance of astrocytes in the brain and of the structure and dynamic properties of intermediate filament proteins. Astrocytes are now recognized as partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 111 publications
1
22
0
1
Order By: Relevance
“…GFAP not only controls astrocytic motility and shape by providing structural stability (Rodnight et al, 1997), Figure 9. Clusters of GLT-1 at GFAP-labeled astrocyte endfeet.…”
Section: Discussionmentioning
confidence: 99%
“…GFAP not only controls astrocytic motility and shape by providing structural stability (Rodnight et al, 1997), Figure 9. Clusters of GLT-1 at GFAP-labeled astrocyte endfeet.…”
Section: Discussionmentioning
confidence: 99%
“…Perisynaptic Schwann cells express muscarinic acetylcholine receptors that normally respond to acetylcholine released from the active nerve terminals, leading to influx of calcium, which in turn down-regulates glial fibrillary acidic protein (GFAP) (Jahromi et al, 1992;Rodnight et al, 1997;Rochon et al, 2001;Georgiou et al, 1999). The down-regulation of GFAP has been linked directly to the lack of processes of perisynaptic Schwann cells in normally innervated muscles (Rodnight et al, 1997;Rochon et al, 2001;Georgiou et al, 1999). Accordingly, upon partial denervation, the perisynaptic Schwann cells at denervated endplates that are no longer exposed to acetylcholine up-regulate GFAP and extend processes.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocyte purity was assessed by assaying for expression of GFAP, an astrocyte marker (57). Immunostaining showed that Ͼ98% of the cultured cells were GFAP positive (Fig.…”
Section: Retinoids In Adult Ratmentioning
confidence: 99%